Physicochemical characterization, extraction and analysis of pectins from fruit of Campomanesia Xanthocarpa B. (Gabiroba) / Caracterização físico-química, extração e análise de pectinas de frutos de Campomanesia Xanthocarpa B. (Gabiroba) - Eliana Beleski Borba Carneiro; Carmen Lúcia de Oliveira Petkowicz; Gilvan Wosiacki; Paulo Irajara B. Carneiro; Marli da Silva Santos (Semina: Ciências Agrárias, 2009)
Campomanesia xanthocarpa Berg. (Myrtaceae) is a Brazilian native tree, with large range of wild natural distribution or as dooryard tree, in the de South Region. It presents enlarge fructification and grows in poor soils at hot or dry climates. The mature fruit is green-yellow, and the pulp is sweet and richest in vitamins, and are used to make juices or eaten fresh. The fruit contains macro and micronutrients: proteins (1.08 g/100 g), fats (0.12 g/100 g), reduces sugar (8.3 g/100 g, being fructose 4.0 g/100g; glucose 4.3 g/100g), mineral salts (iron 3.52, calcium 28.45, phosphorus 25.3 mg/100g, potassium 1.53mg/100g). The high contents of phenolic compounds (1616 ppm/100g) and vitamin C (233.56 mg/100g) is remarkable indicating this fruit as functional food. The succulent pulp and fruit characteristic flavor can be taken as advantage in the preparation of frozen pulp and an excellence raw material to preparation of juices, jellies, ice creams etc. The fruit texture can be attributed to pectin contents that was extracted and analyzed. This fruit has technological potential due to sensorial and nutritious properties. Campomanesia xanthocarpa Berg (Myrtaceae) é uma árvore nativa brasileira, com ampla distribuição natural ou cultivada em pomares domésticos da Região Sul. Apresenta abundante frutificação, cresce em solos pobres, em climas quentes ou secos. A fruta madura é verde-amarelada, a polpa é doce, rica em vitaminas, utilizada para o preparo de sucos ou ingerida in natura. O fruto contém macro e micronutrientes: proteínas (1,08 g/100 g), lipídios (0,12 g/100 g), açúcares redutores (8,3 g/100 g, sendo frutose 4,0 g/100g; glucose 4,3 g/100g), sais minerais (ferro 3,52, cálcio 28,45; fósforo 25,3; potássio 1,53mg/100g). Os elevados teores de compostos fenólicos (1616 ppm/100g) e vitamina C (233,56 mg/100g) qualificam o fruto como alimento funcional. A polpa suculenta e o aroma característico do fruto podem ser atributos vantajosos na preparação de polpa congelada e como excelente matéria-prima no preparo de sucos, geléias, sorvetes etc. A textura do fruto pode ser atribuída ao alto teor de pectinas, que foram extraídas e analisadas. Este fruto apresenta potencial tecnológico devido às suas propriedades sensoriais e nutritivas.